The “BOUSSOLE” Buoy—A New Transparent-to-Swell Taut Mooring Dedicated to Marine Optics: Design, Tests, and Performance at Sea - Antoine, David; Guevel, P.; Desté, J.; Bécu, G.; Louis, F.; Scott, A.; Bardey, P. (American Meteorological Society, 2008)
A new concept of oceanographic data buoy is described, which couples a taut mooring and a “transparent-to-swell” superstructure, and is specifically designed for the collection of radiometric quantities in offshore environments. The design of the thin superstructure addresses two major requirements: stabilizing the instruments in the water column and avoiding shading them. The development of the buoy is described, starting with the theoretical assessment and then describing the various stages of development leading to the latest version of the mooring and buoy. Its performance at sea is also analyzed. This new platform has been deployed in the deep waters (2400 m) of the northwestern Mediterranean Sea for about 4 yr (since September 2003) and provides a quasi-continuous record of optical properties at this site. The data are used for bio-optics research and for calibration and validation operations of several European and U.S. ocean color satellite missions. The plan is to continue the deployment to build a decadal time series of optical properties. The instrument suite that is installed on this buoy is also briefly described, and sample results are shown to demonstrate the ability of this new system to collect the data at the desired frequency and quality.